2016
DOI: 10.1190/geo2015-0194.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal maturity on elastic properties of kerogen

Abstract: We have performed spatially continuous nanodynamic mechanical analysis on four organic-rich shale samples with different thermal maturities to extract the elastic modulus of the kerogen particles. Aliquots were rigorously prepared, and three scans were acquired from each aliquot. Subcritical nitrogen adsorption pore characterization was performed to determine the abundance of kerogen-hosted porosity. To fully characterize the pore system of samples from the oil window, toluene and then chloroform extraction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…1 A ). This decrease of rigidity with thermal maturity is confirmed by experimental indentations (19).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…1 A ). This decrease of rigidity with thermal maturity is confirmed by experimental indentations (19).…”
Section: Resultssupporting
confidence: 67%
“…The presence of hierarchical structures of organic hosted pores evolving through thermal maturation, as probed in scanning electron microscopy (5, 13), small-angle neutron scattering (1417), and adsorption (3, 14, 18), may affect the overall properties. For example, at an experimental macroscopic scale, the organic porosity has been found to be responsible for a significant reduction of the kerogen particle modulus with respect to thermal maturation (19). In addition, the analysis of gas adsorption isotherms demonstrates that thermal maturity of the organic matter affects the surface area, pore volume, and geometrical permeability (3, 14, 18, 20).…”
mentioning
confidence: 99%
“…We hypothesize that these cracks form due to increasing pressure from kerogen decomposition, with differential expansion providing nucleation cites at the interfaces between phases. The fluid pressure in the pore space of kerogen may also influence crack formation [ Zargari et al , ], but was difficult to investigate in our study.…”
Section: Resultssupporting
confidence: 56%
“…Nanoindentation studies on shales with maturity suggest that there is a reduction in effective Young's modulus with increased maturity (Shukla et al, 2013; Zargari et al, 2016) caused by the development of organic intraparticle pores from bitumen generation and migration. If this were to be the case, it would be expected that the proportion of higher modulus values and overall modulus values would decrease with maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Effective elasticity is affected directly by porosity in studies using both acoustic wave velocity (Allan et al, 2014, 2016; Suwannasri et al, 2018) and nanoindentation, whereby derived organic matter Young's modulus decreases from 20 to 7–12 GPa (Zargari et al, 2016). However, in higher‐resolution studies using AFM, an increase in organic matter Young's modulus is observed with maturity (Emmanuel et al, 2016a; Goodarzi et al, 2017; Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%